Design, Automation &Amp; Test in Europe Conference &Amp; Exhibition (DATE), 2014 2014
DOI: 10.7873/date.2014.147
|View full text |Cite
|
Sign up to set email alerts
|

Integrated microfluidic power generation and cooling for bright silicon MPSoCs

Abstract: Abstract-The soaring demand for computing power in our digital information age has produced, as an undesirable sideeffect, a surge in power consumption and heat density for Multiprocessors Systems-on-Chip (MPSoCs). The resulting temperature rise results in operating conditions that already preclude operating all the cores at maximum performance levels, in order to prevent system overheating and failures. With more power demands, MPSoCs will face a power delivery wall due to the reliability limitations of the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Mohamed M. Sabry et al demonstrated the potential of power delivery and cooling issues, caused by limitations in Dennard scaling, using a disruptive approach for integrated power generation and cooling based on multiprocessor SoCs. Indeed, this new approach used the coolant fluid as a means of delivering energy to the chips [ 46 ]. Wen Yueh et al presented the design, experimental characterization, and feasibility analysis of integrated in-package fluidic cooling for mobile SoCs.…”
Section: Microfluidic Cooling Application In Specific Applicationmentioning
confidence: 99%
“…Mohamed M. Sabry et al demonstrated the potential of power delivery and cooling issues, caused by limitations in Dennard scaling, using a disruptive approach for integrated power generation and cooling based on multiprocessor SoCs. Indeed, this new approach used the coolant fluid as a means of delivering energy to the chips [ 46 ]. Wen Yueh et al presented the design, experimental characterization, and feasibility analysis of integrated in-package fluidic cooling for mobile SoCs.…”
Section: Microfluidic Cooling Application In Specific Applicationmentioning
confidence: 99%
“…Flow Cell Array (FCA) technology, first introduced in [8], is a microfluidic channel-based solution for thermal and power management of 3D ICs, combining power generation and on-chip liquid cooling. It has emerged as a promising approach to solve heat dissipation and power delivery problems of 3D integration [9]. FCAs are able to transform absorbed heat into additional power, as electrochemical reactions between electrolytes inside the channels are accelerated with temperature [10].…”
mentioning
confidence: 99%